ORAL STORIES ABOUT THE WAR IN RAZDORSKAYA, UST-DONETSK REGION, ROSTOV REGION: THE GENERAL AND THE LOCAL (BY THE MATERIALS OF THE SUMMER 2010 EXPEDITION) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-104-118Dedicated to the blessed memory of T. B. DianovaThe article analyzes texts that allow to identify common and local features in the memoirs of the Great Patriotic War, some interesting unique motifs are noted. The purpose of the study is to show these features on the examples of fragments of oral stories of a particular settlement, in front of the eyes of the inhabitants of which hostilities took place, as a result of which people had to survive, save relatives and friends, acquired property, interact with neighbors, make moral choices, help the Soviet people to the best of their ability. soldiers and coexist with enemies. The motifs characteristic of oral stories about the war recorded in different regions, unique and belonging to the folklore tradition, are singled out.Key words: Great Patriotic War, oral stories, local, common places, unique in memories, field practice